EVALUATION OF SELECTED HIGH RANK COAL IN KUTAI BASIN, EAST KALIMANTAN RELATING TO ITS COKING PROPERTIES - Bukin Daulay; Binarko Santoso; Nining Sudini Ningrum (Puslitbang tekMIRA, 2015)
Abundant coal seams of Miocene age with thickness of up to 4.7 metres occur in Kutai Basin, East Kaliman- tan. Selected coals are analyzed in order to evaluate its coking properties. The coals have bituminous in rank with calorific value of 5,582-8,357 kg/kcal (adb) and vitrinite reflectance of 0.57-0.97%. These selected high rank coals are normally concentrated in high gradient temperature zone or proximity to intrusive body. Vitrinite reflectances of these coals are lower than those of Australian coking coals (1.04-1.06%), but higher than of Indonesian normal coalification coals. Vitrinite is the dominant maceral in coals from Kutai Basin (73-96%), while inertinite and liptinite are only present in small amount, i.e. trace-10.2% and trace-8.2%, respectively. In contrast, vitrinite is lower and inertinite is higher in Australian coking coals, i.e. 64.8- 79.0% and 18.4-31.6%, respectively. Generally, crucible swelling number of Kutai Basin coals is lower than of Australian coking coals. Based on its vitrinite reflectance and calorific values, some of selected high rank coals from Kutai Basin have developed semi coking properties. The enhancement of rank is probably due to the effect of igneous intrusions or high gradient temperature. However, vitrinite content of the coals is higher than of coking coal range. Crucible swelling number of the coal is also too low, except for sample EK 1 and EK 2 which have CSN too much of 6 and 4, respectively. Therefore, the coals are not categorized as prime coking coal, but they can be blended with bituminous inertinite rich coals to make metallurgical coke for blast furnace.